Are speech and language therapists included in stroke teams? A Systematic review - Pastou, Georgia (My University, 2024)
Stroke is the second leading cause of death worldwide and the primary cause of acquired disability in adults. Stroke survivors often experience some form of permanent disability, with a significant percentage facing severe difficulties in carrying out daily activities. Speech and language therapists play a crucial role in stroke teams by assessing speech production, language comprehension, and expression deficits. They then create personalized therapy plans to meet patients' unique needs and objectives. The impact of a country's income level on the role of speech and language therapists in stroke teams varies significantly, affecting access to specialized services and the ability to provide comprehensive rehabilitation support for stroke survivors. This systematic review aimed to determine the direct involvement of speech and language therapists in stroke teams based on the country's income level.
Keywords: team; speech and language therapists; Systematic review; stroke; ομάδα; λογοθεραπευτές; συστηματική ανασκόπηση; εγκεφαλικό